Stability and change in levels of work–family conflict: A multi‐study, longitudinal investigation. Issue 1 (31st October 2021) - Smith, Claire E.; Wayne, Julie Holliday; Matthews, Russell A.; Lance, Charles E.; Griggs, Tracy L.; Pattie, Marshall W.
Abstract : There has been little theoretical and empirical attention to the role of time in studying levels of work–family conflict. Contrary to theoretical assumptions that work–family conflict is a highly dynamic construct, we borrow from established theories to describe a Stability and Change Model, which posits that work–family conflict levels are primarily stable with some meaningful change over time. The proposed model also outlines predictors of stability (and change) in work–family conflict levels: stability (or change) in‐person (i.e., neuroticism) and situational factors (i.e., role demands and, to a lesser extent, resources). Findings across two longitudinal studies with timeframes of 5 months (one‐month lags) and 3 years (one‐year lags) suggest that 75–80% of the observed variance in work–family conflict levels is stable over mid‐ to long‐term timeframes. In line with our Stability and Change Model, trait‐state‐occasion modelling results indicate that stability in work–family conflict is primarily due to stability in workload demands and to a lesser extent, personality factors (i.e., neuroticism), but, unexpectedly, not resources. There was some meaningful change in work–family conflict levels over time, primarily due to changes in demands and to a lesser extent, changes in person characteristics. Theoretical, methodological, and analytical considerations for future studies of work–family conflict levels are discussed. Practitioner points: WFC levels may be very resistant to change. Our findings highlight the importance for organizations to make a sustained commitment to addressing factors that might create WFC rather than short‐term efforts. Organizations may design impactful interventions by aiming to significantly and durably reduce job demands, specifically: ○ High involvement work practices that foster empowerment, information sharing, rewards, and training have been shown to reduce job demands including role overload (Kilroy et al., 2016, Human Resource Management Journal, 26, 408). ○ Supervisors could reduce workload by eliminating unnecessary tasks or prioritizing most important tasks and/or developing employees' time management skills so they can accomplish important job tasks in the time available. ○ Reducing hindrance stressors such as role ambiguity and hassles tend not to be as relevant. Organizations may also want to consider person variables (e.g., personality, affect) by training for individual characteristics that may help employees manage WFC such as mindfulness training.